Importance of Serum Adiponectin Levels in The Prediction And Ethiopathogenesis of Intrauterine Growth Restriction - Karlı, Pervin; Başbuğ, Alper; Kılıç, Çiğdem; Kutluer, Gülşen; Artar, İshak and Gülerman, Hacer Cavidan (Journal of Medical Biomedical and Applied Sciences, 2018)
Objective: Our aim in this study is to determine the possibility that patients with IUGR (intrauterine growth retardation) will be able to look at the adenonetin levels in the early stages of pregnancy and to have IUGR. In this respect, early diagnosis, treatment and follow-up are aimed to reduce morbidity and mortality due to IUGR Material Method: The study was carried out between January and March 2010. Zekai Tahir Burak Women’s Health Education and Research Hospital 28-40. with 89 patients aged 18-40 years. Groups 44 IUGR patients and 45 normal pregnant patients were divided into two groups. To examine the serum adiponectin level, an average of 3 cc was taken in the gel biochemistry tubes and then centrifuged at 4000 10 minutes. The resulting serum samples were collected for the ELISA kit and kept at -80 C until the day the patients were collected. In the study, adiponectin levels were measured by serum ELISA (enzyme linked immunosorbent assay) method. Results: In adiponectin evaluation, mean value was 105.90 19.02 pg / ml for the IUGR group, 65.96 16.5 pg / ml for the control group and 1.6 times higher for the IUGR group( p < 0.001) Conclusion: In this study, the increased adiponectin levels of IUGR patients were significantly higher than those of IUGR patients, suggesting that pregnancies of IUGR patients can be measured high in the first weeks and if IUGR is high in those weeks, IUGR can be predicted.